Soft union bi-quasi-interior ideals of semigroups - BAŞ, Zeynep Hare; SEZGİN, Aslıhan; STOJANOVİĆ, Nenad (Jurnal Matematika Integratif, 2025)
The concept of the soft union (S-uni) bi-quasi-interior ₿ꝖĪ) ideal of semigroups is proposed in this study, along with its equivalent definition. We derive the relationships between S-uni ideals and S-uni ₿ꝖĪ ideal. The S-uni ₿ꝖĪ ideal is shown to be S-uni bi-ideal, left ideal, right ideal, interior ideal, quasi-ideal, bi-interior ideal, left/right bi-quasi ideal, and left/right quasi-interior ideal. It is shown that certain additional requirements, such as regularity or right/left simplicity, are necessary for the converses, and counterexamples are given to demonstrate that the converses are not true. Additionally, it is demonstrated that the soft anti characteristic function of a subsemigroup of a semigroup is an S-uni ₿ꝖĪ ideal if the subsemigroup itself is a ₿ꝖĪ ideal, and vice versa. Consequently, a significant connection between soft set theory and classical semigroup theory is established. Additionally, it is demonstrated that while the finite soft OR-products and union of S-uni ₿ꝖĪ ideals are also S-uni ₿ꝖĪ ideals, the intersection and finite soft AND-products are not. A broad conceptual characterization and analysis of S-uni ₿ꝖĪ ideals are presented in this paper.